Feline dental implants: new paradigm shift in maxillary alveolar osteitis treatment planning with osseodensification - Mele, R. E.; Kurtzman, G. M. (Journal of Osseointegration, 2019)
Background Felines are obligate carnivores and use their teeth for prehending as well as tearing and dissecting their food. Mastication is the first step of digestion, aiding in the lubrication of the food and the formation of a bolus. Mastication also increases the surface area of the food to be initially digested by salivary enzymes before being more easily swallowed. The teeth are specialized structures which play an important role in mastication, grooming, supporting the lips and the tongue, as well as being used as weapons for hunting and for self-defense. Although some mammals can still survive with few or no teeth at all, cats included, losing teeth can influence the types of foods that can be eaten, and will affect the ability to masticate and processing of the food prior to swallowing. Dental implants have become an option for replacement of lost canines in these animals. Although cats appear to manage well after a canine extraction, complications such as lip entrapment can occur, especially after maxillary canine tooth extraction. Even cats with a complicated crown fracture of the maxillary canine tooth that have had root canal therapy to preserve the tooth, can still suffer from lip entrapment. This can lead to painful lip ulcers and the need for further dental treatment. Today, canine tooth replacement with a dental implant/crown is a predictable option that can be offered to clients who would like to replace a lost canine tooth. Case report Two long term cases and follow up of lost maxillary canines caused by alveolar osteitis and replacement by dental implants, to restore normal function in feline subjects are reported. Conclusion Dental implants proved to be a viable long-term treatment option in the 2 cats described.Immediate implant placement at the time of extraction helps to maintain the surrounding bone structures and prevent collapse of the labial buccal plate. So far, the authors have placed 30 implants in 15 feline subjects up to a 3-year follow-up and no integration failures have been observed to date.